2017
DOI: 10.1002/pon.4409
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and posttraumatic growth after breast cancer: A dyadic approach

Abstract: Findings support the assessment of the couple dyadically and corroborate an attachment approach of the couple as an interdependent unit. Implications of the study for interventions assisting couples in oncological setting are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Ávila et al. (2017) examined associations between attachment and post‐traumatic growth under attachment theory and found that secure attachment was associated to post‐traumatic growth; in contrast, insecure attachment, encompassing anxiety and avoidance, was not found to be related to post‐traumatic growth. In Turner et al.’s (2018) study, optimism and social support were direct factors to post‐traumatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Ávila et al. (2017) examined associations between attachment and post‐traumatic growth under attachment theory and found that secure attachment was associated to post‐traumatic growth; in contrast, insecure attachment, encompassing anxiety and avoidance, was not found to be related to post‐traumatic growth. In Turner et al.’s (2018) study, optimism and social support were direct factors to post‐traumatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Az emlőrákos nők nagy százaléka említi azon félelmeit, hogy a betegséggel járó testi változások miatt esetleg elhagyja őket a partnerük, majd ebből fakadóan alacsonyabb önértékelésről, rosszabb mentális és testi egészségről, partnerkapcsolati és szexuális eredetű nehéz ségekről számolnak be. A vizsgálati eredmények alapján elmondhatjuk, hogy azok a személyek bíznak kevésbé párkapcsolatukban, akiknek kötődési stílusa bizonytalan [29][30][31]. Emlőrákosok alkalmazkodási nehéz ségeit kívánta feltárni az a kutatás, amelyben a bizonytalan kötődés elkerülő és szorongó aldimenzióinak az életminőséggel való kapcsolatát vizsgálták.…”
Section: A Felnőttkori Kötődési Stílus Vizsgálatai Emlőrákos Betegek unclassified
“…Többváltozós elemzéseink alapján elmondható, hogy minél jobbnak ítéli az egyén az egészségi állapotát, minél inkább jellemző a személyre a biztonságos kötődés és minél kevésbé az elkerülő vagy a szorongó kötődés, annál nagyobb a kapcsolati elégedettsége. Ez az összefüggés megerősíti az általános felnőtt [19,20], illetve az emlődaganatos mintákon végzett korábbi kutatások eredményeit [29][30][31]: azok a diagnosztizált nők, akikre jellemzőbb a szorongó, illetve az elkerülő kötődés, kevésbé elégedettek párkapcsolatukkal, ami megegyezik a szakirodalomban leírtakkal [31,32,41]. A többváltozós elemzés egyúttal azt is jelezte, hogy a diagnózis megléte, a többi változóra kontrollálva, már nem jelzi előre a kapcsolati elégedettséget.…”
Section: A Kapcsolati éS Szexuális Elégedettség Prediktoraiunclassified
“…Secure attachment was positively related to PTG, and avoidant attachment was negatively related to PTG (Lev-Ari & Levi-Belz, 2019). Similarly, a study by Avila et al (2017) indicated that the partner's attachment security supported the individual's positive adjustment to life after breast cancer. Researchers concluded that having a securely attached partner relationship can provide resources for an individual’s PTG beyond those available to the individual alone (Avila et al, 2017).…”
Section: Perinatal Loss and Partner Supportmentioning
confidence: 97%